2002
DOI: 10.1046/j.1365-2133.2002.04692.x
|View full text |Cite
|
Sign up to set email alerts
|

Eczema: quality of life by body site and the effect of patch testing

Abstract: Patients confirmed as having contact allergy show a subsequent improvement in eczema severity and an improvement in quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
73
5
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(83 citation statements)
references
References 11 publications
3
73
5
2
Order By: Relevance
“…A mean DLQI at 7.8 for severe OHE patients is in accordance with earlier findings and rank the disease just below AD and psoriasis (15,22,25,28). The extent of impairment in QoL for the whole group (mean total DLQI score of 5.5) was influenced by the fact that 1/3rd of the group had no longer active eczema or only minimal activity at the time they answered the questionnaire.…”
Section: Discussionsupporting
confidence: 76%
“…A mean DLQI at 7.8 for severe OHE patients is in accordance with earlier findings and rank the disease just below AD and psoriasis (15,22,25,28). The extent of impairment in QoL for the whole group (mean total DLQI score of 5.5) was influenced by the fact that 1/3rd of the group had no longer active eczema or only minimal activity at the time they answered the questionnaire.…”
Section: Discussionsupporting
confidence: 76%
“…A literatura traz dados variados em relação à importância da gravidade da doença, apresentando trabalhos em que a qualidade de vida não está relacionada a esta variá-vel21, outros em que a extensão da visibilidade é mais importante que a gravidade, 22 ou ainda de que a qualidade de vida não varia de acordo com o local do corpo afetado, mas proporcionalmente à percepção de gravidade por parte do paciente. 23 Levando em consideração a exposição ao outro a que fica submetido o indivíduo com problema dermatológico, alguns autores indicam a necessidade de adaptação à doença. 24 Faz-se necessário considerar as características de personalidade dos sujeitos, visto que a forma como o indivíduo percebe e interpreta as situações ao seu redor, inclusive a própria dermatose, é influenciada por suas características pessoais.…”
Section: Resultados Dados Sócio-demográficosunclassified
“…Studies have shown that asthma, eczema and rhinitis have a negative impact on quality of life (QoL) [8][9][10][11][12][13][14][15][16]. Consistent and successful avoidance of the offending foods, however, limits the influence on individuals' physical health.…”
Section: Introductionmentioning
confidence: 98%